Vibration and stability analysis of rotor-bearing-pedestal system due to clearance fit. (1st November 2019) - Cao, Hongrui; Shi, Fei; Li, Yamin; Li, Bijian; Chen, Xuefeng
Highlights: A fully dynamic model of rotor-bearing-pedestal system is proposed. The model combines rigid body element, dynamic bearing model and lumped mass model. The nonlinear phenomenon is overserved quantitatively. Abstract: Rotor-bearing-pedestal systems are key components of rotating machinery. In this paper, a dynamic model of rotor-bearing-pedestal system is proposed to investigate the vibration characteristics and stability due to fit clearance. Considering the fit clearance between the bearing outer ring and pedestal, the bearing dynamic model, rotor rigid element model and lumped mass model of the pedestal are coupled to establish the dynamic model of rotor-bearing-pedestal system with fit clearance. Experiments are conducted on a rotor test rig which is supported by two angular contact ball bearings. Good agreements between measurement and simulation verify the accuracy of the proposed dynamic model. Based on this model, time displacement responses and Fourier spectra are used to analyze the vibration characteristics of rotor system. The phase trajectory plots are used to illustrate the stability changes of the system under the influence of the fit clearance.